EXPLORING SELF-DIRECTED LEARNING THROUGH ENGLISH LEARNING JOURNALS AMONG VOCATIONAL STUDENTS - Dewi Suryanti; Fajar Pudo (Universitas PGRI Palembang, 2025)
In the realm of English language education for vocational students, cultivating self-directed learning is pivotal in equipping learners with the skills necessary for lifelong learning. This study investigates the extent to which weekly learning journals, composed over a three-week period by 50 vocational students, reflect their self-directed learning behaviors beyond the classroom setting. Employing a qualitative methodology through thematic analysis, the research identified three key themes recurring in the journal entries: recognition of learning needs, self-evaluation, and the use of learning strategies. The predominant theme was students’ awareness of their learning needs, with particular emphasis on difficulties in comprehending and applying English tenses an area that frequently became the focus of their independent study efforts. The second theme pertained to students’ reflective evaluation of their learning progress and areas requiring improvement. The least represented theme involved strategic planning, including the selection of methods or tools to enhance language proficiency. These findings indicate that the students are in the initial phase of developing autonomous learning, showing a foundational awareness of their challenges but lacking the consistent application of deliberate strategies that characterize mature self-directed learners. The study underscores the importance of structured pedagogical support to nurture greater autonomy and strategic engagement in English language learning among vocational students.